2020
DOI: 10.1007/s10113-020-01622-9
|View full text |Cite
|
Sign up to set email alerts
|

Climate resilience of the top ten wheat producers in the Mediterranean and the Middle East

Abstract: Wheat is the main staple crop and an important commodity in the Mediterranean and the Middle East. These are among the few areas in the world where the climate is suitable for growing durum wheat but also are among the most rapidly warming ones, according to the available scenarios of climate projections. How much food security and market stability in the Mediterranean and the Middle East, both depending on wheat production and its interannual variability, are going to be compromised by global warming is an ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 51 publications
(85 reference statements)
0
21
0
Order By: Relevance
“…This study provides a theoretical framework for addressing quantitative aspects of resilience and sustainability of real crop production systems using models and observed data for different world regions and at the global scale in the context of climate change ( Zampieri et al, 2019 , Zampieri et al, 2020 ). While most adaptation studies often neglect the importance of inter-annual crop production variability ( Challinor et al, 2014 ), our theoretical findings demonstrate how it can be accounted in order to assess resilience.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study provides a theoretical framework for addressing quantitative aspects of resilience and sustainability of real crop production systems using models and observed data for different world regions and at the global scale in the context of climate change ( Zampieri et al, 2019 , Zampieri et al, 2020 ). While most adaptation studies often neglect the importance of inter-annual crop production variability ( Challinor et al, 2014 ), our theoretical findings demonstrate how it can be accounted in order to assess resilience.…”
Section: Discussionmentioning
confidence: 99%
“…While most adaptation studies often neglect the importance of inter-annual crop production variability ( Challinor et al, 2014 ), our theoretical findings demonstrate how it can be accounted in order to assess resilience. If the stability of the production time series is measured by the reciprocal of the coefficient of variance of the production time series, we have demonstrated that the resilience indicator proposed is the square of the stability ( Zampieri et al, 2019 ) and we provided a definition that can be applied to non-stationary time series characterizing agricultural production ( Zampieri et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations